[OP.3A.04] REDUCED CORTICAL OXYGENATION PREDICTS PROGRESSIVE RENAL FUNCTION DECLINE IN HUMANS. (September 2017) - Pruijm, M.; Milani, B.; Pivin, E.; Podhajska, A.; Vogt, B.; Stuber, M.; Burnier, M.
Abstract : Objective: Renal tissue hypoxia is generally considered as the common final pathway in the development and progression of chronic kidney disease (CKD). BOLD-MRI studies have recently demonstrated that CKD patients have higher cortical R2 * values (corresponding to lower oxygenation) than controls. Whether cortical oxygenation as measured with BOLD-MRI predicts renal function decline is unknown. Design and method: Blood-oxygenation level dependent MR imaging was performed under standardized conditions in a cohort of 112 CKD patients, 47 hypertensives and 24 controls. Images were analyzed with the twelve-layer concentric objects method (TLCO) that divides renal parenchyma in 12 layers of equal thickness, and reports the mean R2 * value of each layer, along with the change in R2 * between successive layers called the R2 * slope. Circulating creatinine values were followed over time and estimated glomerular filtration rate (eGFRcreatinine) was used to calculate the yearly change in glomerular function. Participants were classified as "progressors" when their eGFR decline was above 3.3 ml/min/1.73m 2 /year. Results: The mean ± SD follow up period was 3.0 ± 1.1 years, and 5.3 ± 2.7 creatinine values were available per individual. The eGFR decline was respectively −2.0 ± 6.0, 0.5 ± 4.9 and −0.2 ± 5.3 ml/min/1.73m 2 /year in CKD, hypertensive patients and controls, and the percentage of progressors 30.2, 18.2 and 16.7%. In multivariable regression analysis adjusted for age, gender, diabetes, RAS blockers, baseline eGFR and proteinuria, the yearly eGFR decline correlated negatively with baseline 24 h proteinuria (regression coefficient β ± SE: −1.41 ± 0.60, p = 0.020) and mean R2 * value of the outer (cortical) layers (β−0.41 ± 0.16, p = 0.013), but not with the other above mentioned covariates. The R2 * slope correlated positively with eGFR decline (β 0.44 ± 0.17, p = 0.012). Similar results were found with logistic regression for the association between "progressor" status and cortical R2 * (OR and 95% CI per R2 * : 1.16 (1.00–1.35), p = 0.047). Conclusions: We demonstrate for the first time in humans that cortical oxygenation as assessed with BOLD-MRI is an independent predictor of renal function decline: the lower baseline cortical oxygenation, the faster the decline of renal function. These data open the road to further studies exploring functional MRI as a tool to predict adverse renal outcome.